Estrutura populacional de Triatoma brasiliensis (Hemiptera, Triatominae) de distintos ecótopos e municípios dos estados brasileiros do Rio Grande do Norte e Paraíba inferida pela variação morfométrica e molecular : Population structure of Triatoma brasiliensis (Hemiptera, Triatominae from different ecotopes and municipalities of the Brazilian states of Rio Grande do Norte and Paraiba inferred from morphometric and molecular variation - Kamimura, Edgard Hiromi, 1989- (2020)
Orientador: Carlos Eduardo Almeida